Isolation and serological identification of enteropathogenic Escherichia coli in pasteurized milk in Brazil Isolamento e identificação sorológica de Escherichia coli enteropatogênica em leite pasteurizado - Zoraide N da Silva; Adriana S da Cunha; Márcia C Lins; Letícia de AM Carneiro; Angela C de F Almeida; Mara LP Queiroz (Universidade de São Paulo, 2001)
OBJECTIVE: To evaluate the microbiological quality of pasteurized milk commercialized in Rio de Janeiro, Brazil, and determine serologically enteropathogenic Escherichia coli (EPEC) strains in E. coli isolates obtained from milk samples. METHODS: Ninety samples of pasteurized milk -- types B and C -- of three different commercial brands, purchased in supermarkets and bakeries in Rio de Janeiro, were examined. The amount of total and fecal coliform bacteria was estimated using the Most Probable Number technique. Mesophilic, psychrotrophic, and thermoduric microorganism counts were determined by the Standard Plate Count technique. Isolation and identification of E. coli were carried out using conventional physiological tests. Commercial antisera were used for serological characterization of EPEC. RESULTS: The three milk brands analyzed revealed bacterial counts above the regulated values of the Brazilian government. It was found that among 208 strains of E. coli isolated, 46 (22.1%) were serologically classified as EPEC. The most common EPEC serogroup was O55 (15.2%). CONCLUSIONS: Though recent studies on virulence factors indicate that not all strains serologically classified as EPEC are able to attaching/effacing lesion, it is believed that the isolation of EPEC serogroups from pasteurized milk represent a potential risk for children, as well as an indicative of the presence of other enteropathogens. OBJETIVOS: Avaliar a qualidade microbiológica de leite pasteurizado comercializado, isolar e identificar sorologicamente cepas de Escherichia coli enteropatogênica clássica (EPEC) nesse alimento. MÉTODOS: Foram estudadas 90 amostras de leite pasteurizado, de três marcas comerciais diferentes, dos tipos B e C, obtidas em padarias e supermercados do Rio de Janeiro, RJ. A contagem de coliformes totais e fecais foi estimada aplicando-se a técnica do número mais provável. A quantificação de microorganismos mesófilos, psicrotróficos e termodúricos foi determinada pela técnica da contagem padrão em placa. A identificação fisiológica de E. coli foi realizada por metodologia convencional e a identificação sorológica de EPEC, com a utilização de soros comerciais. RESULTADOS: As três marcas de leite pasteurizado apresentaram contagens bacterianas acima do padrão permitido pela legislação brasileira. Foram isoladas 208 cepas de E. coli, entre as quais 46 (22,1%) foram sorogrupadas como EPEC. O sorogrupo mais freqüente foi o O55 (15,2%). CONCLUSÕES: Apesar de estudos recentes sobre fatores de virulência indicarem que nem todas as cepas sorogrupadas como EPEC são capazes de causar a lesão A/E (attaching/ effacing), considerou-se que o isolamento de sorogrupos de EPEC, nesse alimento, representa risco potencial para crianças e, também, possível meio de veiculação de outros enteropatógenos.